KONSEP MAQASID SYARIAH KONTEMPORER (Studi Komparasi Pemikiran Ibnu Asyur dan Alal Al-Fasi) - Ziadul Ulum Wahid; Dzulfikar Rodafi; Nurhasan Nurhasan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
This article attempts to compare between two toughts of contemprorary figure; Muhammad Thohir Ibnu 'Asyur dan 'Alal Al Fasi. Those two figures are the reformers of Maqashid Syari'ah concept that initiated by Imam Syathibi. This research focuses on;1. how is the contemporary concept of Maqashid Syari'ah based on Muhammad Thohir and 'Alal Al Fasi perspective, 2. what is the fundamental distinction between Ibnu A'syur's theory and 'Alal Al Fasi's theory, and the implication of them through contemporary study of Maqashid Syari'ah?. this researh applies approach study of comparative analysis that is referred to primary data such as two monumental books; Maqashid Syari'ah Al-Islamiyah, Maqashid Syari'ah Al-Islamiyah wa ma karimuha. in other hand, this research also uses supporting data that are interrelated such as classic literature, article, journal, and thesis. the main point that is discovered in this research, is only in aspect of methodology. Ibnu Asyur Attempts to reconsructs Imam Syatibi's thought, and it was proved by how ibnu asyur maps Dharuriyyatul khams. while 'Alal Al Fasi only discusses Imam Syatibi's thought back, and it is visible on Al Fasi's work. he always cites Imam Syatibi in his thought without creating any reformation in Maqashid Syari'ah discourses. Keyword : Maqashid Syariah, contemprorary, Ibnu ‘Asyur, ‘Alal Al-Fasi